Relationships Among Attachment, Cohesion, Interpersonal Learning and Outcomes in Group Psychotherapy for Binge Eating Disorder - Gallagher, Meagan (Université d'Ottawa / University of Ottawa, 2013)
The current dissertation is comprised of two studies that examined the relationship between group dynamics, attachment anxiety, and post-treatment outcomes in a sample of women (N = 102) with binge eating disorder (BED) who received Group Psychodynamic Interpersonal Psychotherapy. The first study explored the relationship between the development of group cohesion, the individuals’ level of attachment anxiety, and frequency of binge eating, symptoms of depression, and self-esteem at post-treatment. The second study explored the relationship between the interpersonal learning, individuals’ level of attachment anxiety, and outcomes. Interpersonal learning was conceptualized as the convergence between multiple perspectives of group cohesion: one’s own and the group’s perception of one’s cohesion to the group. Parallel measures of individual self-rated cohesion (CQ-I) and mean group-rated cohesion (CQ-G) were developed based on the original Cohesion Questionnaire (CQ; Piper et al., 1983) for this study. Participants were assigned to homogeneous groups composed of either high or low attachment anxiety to assess the impact of pre-treatment attachment anxiety. Findings indicated significant growth in cohesion over time, and a significant convergence in multiple ratings of cohesion. These processes did not differ significantly based on level of attachment anxiety. Growth in cohesion was related to greater reductions in binge eating for those high in attachment anxiety, while the convergence in ratings of cohesion (i.e., interpersonal learning) was related to improvements in self-esteem for individuals in both attachment anxiety conditions. The findings support the importance of group interventions for BED that are sensitive to individuals’ attachment anxiety, and that emphasize cohesiveness, and interpersonal learning to improve outcomes.
Keywords: group psychotherapy; binge eating disorder; cohesion; interpersonal learning